Preparation method and application of high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material
By preparing highly active endogenous nitrogen-doped biochar-zero-valent iron composites, using agricultural residues and potassium carbonate, combined with high-energy mechanical ball milling technology, the problem of low Cr(VI) removal efficiency in water bodies is solved, achieving high efficiency, Economical pollutant removal effect.
Patent Information
- Application Number
- CN202411447175.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively remove hexavalent chromium (Cr(VI) pollution in water bodies, especially because the low specific surface area of zero-valent iron (ZVI) limits its mass transfer efficiency, and exogenous nitrogen doping increases energy consumption and Preparation complexity.
Using the preparation method of highly active endogenous nitrogen-doped biochar-zero-valent iron composite, the abundant protein in agricultural residue bean residue as nitrogen source, potassium carbonate is used to make pores, and through high-energy mechanical ball milling technology, microns are zero. Valid iron powder is doped with biochar to form a composite material with a high specific surface area.
It improves the adsorption effect of composite materials on Cr(VI) and electron transfer efficiency, and realizes the rapid removal of Cr(VI) in water. It has the characteristics of low cost, simple operation and high safety, and is suitable for large-scale production applications.
Smart Images

Figure CN119118336A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water pollution remediation, and in particular to a preparation method and application of a high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material. Background Art
[0002] Metal Cr is widely used in electroplating, petroleum refining, metallurgy and leather making. Due to the lack of reasonable and effective control measures, Cr is inevitably released into the environmental medium. In recent years, Cr has become the fourth most common heavy metal in China's wastewater. Among them, hexavalent chromium (Cr(VI)) has higher toxicity, stability, solubility and migration ability than trivalent chromium (Cr(III)). The emission and migration of Cr(VI) pose serious risks to both the human body and the natural environment. The World Health Organization (WHO) stipulates that the concentration of Cr(VI) in drinking water shall not exceed 0.05 mg / L. Therefore, it is urgent to develop environmental functional materials that can effectively remove Cr(VI) from water bodies.
[0003] To date, researchers have developed a variety of Cr(VI) treatment technologies, such as precipitation, coagulation, reduction and ion exchange. Among them, zero-valent iron (ZVI) can quickly and greenly remove Cr(VI) from water bodies. However, the low specific surface area of ZVI limits its mass transfer efficiency to pollutants. To solve this problem, researchers have modified ZVI by surfactants or polymers or constructed ZVI-carbon composites to improve the electron transfer efficiency during Cr(VI) reduction. Biochar is a stable solid porous material with a large specific surface area, abundant surface functional groups and adjustable surface structural properties, making it an ideal carrier for ZVI. In addition, relevant studies have shown that nitrogen (N) species in biochar can effectively disrupt the charge distribution of the carbon layer, improve the conductivity of biochar and its adsorption efficiency for pollutants. However, exogenous N doping inevitably brings higher energy consumption and more complicated preparation processes. Therefore, the development of an endogenous nitrogen-doped biochar-zero-valent iron composite with a high specific surface area is conducive to the efficient removal of Cr(VI) in water bodies. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a preparation method and application of a high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material. The prepared composite material is not only low-cost and simple in synthesis method, but also effectively improves the specific surface area and active sites of the material, which on the one hand improves the adsorption effect on Cr(VI), and on the other hand improves the electron transfer efficiency between the composite material and Cr(VI).
[0005] In order to solve the above technical problems, the first technical solution adopted by the present invention is: to provide a method for preparing a high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material, comprising the following steps: (1) Taking agricultural residue bean curd residue as a precursor, washing it with deionized water for several times and then drying it, and grinding the dried bean curd residue into fine powder; (2) Weighing a certain amount of potassium carbonate and mixing it with the okara powder prepared in step (1) to form a solution, vigorously mixing the prepared potassium carbonate solution and the okara powder at room temperature for a certain period of time and then drying; (3) grinding the obtained dried product, placing the sample in a covered crucible and pyrolyzing it in an oxygen-limited environment of a muffle furnace to produce biochar; (4) The obtained biochar material is mixed with hydrochloric acid and stirred for a certain period of time to remove residual potassium carbonate, and the sample is repeatedly washed with deionized water until it is neutral; (5) Add micron zero-valent iron powder and biochar in a certain proportion into a planetary ball mill and grind them to obtain a composite material.
[0006] In a preferred embodiment of the present invention, in steps (1) and (3), the ground products are sieved through a 100-mesh sieve.
[0007] In a preferred embodiment of the present invention, in step (2), the mass ratio of potassium carbonate to okara powder is 2:1.
[0008] In a preferred embodiment of the present invention, in step (3), the calcination heating rate in the muffle furnace is 5-10°C / min, the calcination temperature is 400-900°C, and the calcination pyrolysis time is 2-4 hours.
[0009] In a preferred embodiment of the present invention, in step (5), the mass ratio of the biochar to the micron zero-valent iron powder is 7:1, the ball milling time is 6 hours, the ball-to-material ratio is 20:1, the ball milling beads are made of zirconium oxide, and the ball milling beads have a diameter of 1-15 mm.
[0010] In order to solve the above technical problems, the second technical solution adopted by the present invention is: to provide a high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material prepared by the preparation method of the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material as described in any of the above items.
[0011] In a preferred embodiment of the present invention, the particle size of the composite material is 30-200 microns, and the specific surface area can reach 84.3792-364.5442 m 2 / g.
[0012] In order to solve the above technical problems, the third technical solution adopted by the present invention is: to provide an application of the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material as mentioned above in the environmental treatment of water pollution.
[0013] In a preferred embodiment of the present invention, the pollutant in the water body is Cr (VI).
[0014] Furthermore, the concentration of Cr (VI) in the water body is 40 mg / L, and the degradation rate of Cr (VI) by the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material is as high as 100%, and the adsorption amount is 77.96 mg / g.
[0015] The beneficial effects of the present invention are: (1) The present invention uses agricultural residue bean dregs as a biochar precursor, utilizes the abundant protein in the bean dregs as a nitrogen source, and uses exogenously added potassium carbonate as a pore-forming agent to prepare endogenous nitrogen-doped biochar with a high specific surface area, which has the characteristics of low cost and simple preparation; (2) High-energy mechanical ball milling (BM) is a low-cost and easy-to-operate material modification method. It agglomerates powder particles by repeated crushing and welding, and a series of mechanical alloying occurs during the process. Compared with the general liquid phase reduction method, ball milling technology can greatly reduce the particle size and improve the reactivity of the composite material by increasing the specific surface area; The present invention uses micron zero-valent iron powder as an iron source and utilizes a ball milling process to dope the prepared biochar into zero-valent iron to prepare a biochar-ZVI composite material. The larger specific surface area and rich surface nitrogen species of the biochar effectively improve the composite material's adsorption effect on Cr(VI) in water. In addition, the biochar is used as a conductor, and its rich nitrogen species and high degree of graphitization promote the electron transfer process from ZVI to Cr(VI). The rapid removal of Cr(VI) in water is achieved, and the process has the characteristics of simple operation, low cost, and high safety, and is suitable for large-scale production applications. (3) Compared with the reported biochar-zero-valent iron composite materials, this composite material has certain advantages in terms of reducing agent dosage and reduction efficiency, and can effectively reduce Cr(VI) in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a SEM image of the okara biochar and composite material prepared in Example 6; Figure 2 is a nitrogen adsorption-desorption curve diagram of the okara biochar and the composite material prepared in Example 6; Figure 3 is the Raman spectra of the composite materials prepared in Examples 1 to 6; Figure 4 is the Fourier infrared spectra of the composite materials prepared in Examples 1 to 6; Figure 5 is the electrochemical impedance diagram of the composite material prepared in Examples 1 to 6; Figure 6 is an XPS graph of Cr species on the surface of the composite material prepared in Example 6 after reaction; Figure 7is an XPS graph of the changes in surface N species of the composite material prepared in Example 6 before and after the reaction; Figure 8 is a graph showing the removal rate of Cr(VI) by the composite materials prepared in Examples 1 to 6; Fig. 9 is a graph showing the removal rate of Cr(VI) by the composite materials prepared in Example 6 and Comparative Examples 1 to 5; Fig.10 This is a diagram showing the effect of cations in water on the reduction of Cr (VI) by composite materials; Fig.11 This is a diagram showing the effect of anions and organic matter in water on the reduction of Cr (VI) by composite materials; Fig.12 This is the effect of temperature on the reduction of Cr (VI) by the composite material; Fig.13 This is a diagram showing the effect of pH value on the reduction of Cr (VI) by the composite material. DETAILED DESCRIPTION
[0017] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0018] The embodiments of the present invention include: Embodiment 1: A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material comprises the following steps: Agricultural residue bean dregs were used as raw materials, washed several times with deionized water and then dried. The dried bean dregs were ground into fine powder. A certain amount of potassium carbonate (with a mass ratio of 2:1 to bean dregs) was weighed to form a solution, and the solution was vigorously stirred with bean dregs powder at room temperature for 4 hours and dried to constant weight. The obtained dry product was placed in a muffle furnace and heated to 400°C at 5°C / min and maintained for 2 hours. The obtained biochar material was mixed and stirred with 2M hydrochloric acid for 4 hours to remove residual potassium carbonate, washed with deionized water to neutrality and dried. The obtained biochar and micron zero-valent iron powder were mixed in a mass ratio of 1:7 and added to a planetary ball mill for ball grinding for 6 hours, with a ball-to-material ratio of 20:1.
[0019] Embodiment 2: A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material comprises the following steps: Take agricultural residue bean dregs, wash them with deionized water several times and then dry them naturally. Grind the dried bean dregs into fine powder. Weigh a certain amount of potassium carbonate (with a mass ratio of 2:1 to bean dregs) to make a solution, stir it vigorously with bean dregs powder at room temperature for 4 hours and dry it to constant weight. The obtained dry product is placed in a muffle furnace and heated to 500℃ at 5℃ / min and maintained for 2 hours. The obtained biochar material is mixed with 2M hydrochloric acid for 4 hours to remove residual potassium carbonate, then washed with deionized water to pH 7 and dried. The obtained biochar and micron zero-valent iron powder are mixed in a mass ratio of 1:7 and added to a planetary ball mill for 6 hours, with a ball-to-material ratio of 20:1.
[0020] Embodiment 3: A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material comprises the following steps: Take agricultural residue bean dregs, wash them with deionized water several times and then dry them naturally. Grind the dried bean dregs into fine powder. Weigh a certain amount of potassium carbonate (with a mass ratio of 2:1 to bean dregs) to make a solution, stir it vigorously with bean dregs powder at room temperature for 4 hours and dry it to constant weight. The obtained dry product is placed in a muffle furnace and heated to 600℃ at 5℃ / min and maintained for 2 hours. The obtained biochar material is mixed with 2M hydrochloric acid for 4 hours to remove residual potassium carbonate, then washed with deionized water to pH 7 and dried. The obtained biochar and micron zero-valent iron powder are mixed in a mass ratio of 1:7 and added to a planetary ball mill for 6 hours, with a ball-to-material ratio of 20:1.
[0021] Embodiment 4: A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material comprises the following steps: Take agricultural residue bean dregs, wash them with deionized water several times and then dry them naturally. Grind the dried bean dregs into fine powder. Weigh a certain amount of potassium carbonate (with a mass ratio of 2:1 to bean dregs) to make a solution, stir it vigorously with bean dregs powder at room temperature for 4 hours and dry it to constant weight. The obtained dry product is placed in a muffle furnace and heated to 700℃ at 5℃ / min and maintained for 2 hours. The obtained biochar material is mixed with 2M hydrochloric acid for 4 hours to remove residual potassium carbonate, then washed with deionized water to pH 7 and dried. The obtained biochar and micron zero-valent iron powder are mixed in a mass ratio of 1:7 and added to a planetary ball mill for 6 hours, with a ball-to-material ratio of 20:1.
[0022] Embodiment 5: A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material comprises the following steps: Take agricultural residue bean dregs, wash them with deionized water several times and then dry them naturally. Grind the dried bean dregs into fine powder. Weigh a certain amount of potassium carbonate (with a mass ratio of 2:1 to bean dregs) to make a solution, stir it vigorously with bean dregs powder at room temperature for 4 hours and dry it to constant weight. The obtained dry product is placed in a muffle furnace and heated to 800℃ at 5℃ / min and maintained for 2 hours. The obtained biochar material is mixed with 2M hydrochloric acid for 4 hours to remove residual potassium carbonate, then washed with deionized water to pH 7 and dried. The obtained biochar and micron zero-valent iron powder are mixed in a mass ratio of 1:7 and added to a planetary ball mill for 6 hours, with a ball-to-material ratio of 20:1.
[0023] Embodiment 6: A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material comprises the following steps: Take agricultural residue bean dregs, wash them with deionized water several times and then dry them naturally. Grind the dried bean dregs into fine powder. Weigh a certain amount of potassium carbonate (with a mass ratio of 2:1 to bean dregs) to make a solution, stir it vigorously with bean dregs powder at room temperature for 4 hours and dry it to constant weight. The obtained dry product is placed in a muffle furnace and heated to 900℃ at 5℃ / min and maintained for 2 hours. The obtained biochar material is mixed with 2M hydrochloric acid for 4 hours to remove residual potassium carbonate, then washed with deionized water to pH 7 and dried. The obtained biochar and micron zero-valent iron powder are mixed in a mass ratio of 1:7 and added to a planetary ball mill for 6 hours, with a ball-to-material ratio of 20:1.
[0024] The endogenous nitrogen-doped biochar-zero-valent iron composite material prepared by this method has a nitrogen content of up to 2.77% and a specific surface area of up to 365.12 m 2 / g.
[0025] Comparative Example 1: On the basis of Example 6, the mass ratio of biochar to micron zero-valent iron ball milling was changed to 1:1, and the other conditions remained unchanged.
[0026] Comparative Example 2: On the basis of Example 6, the mass ratio of biochar to micron zero-valent iron ball milling was changed to 2:1, and the other conditions remained unchanged.
[0027] Comparative Example 3: Based on Example 6, the mass ratio of biochar to micron zero-valent iron ball milling was changed to 3:1, and the other conditions remained unchanged.
[0028] Comparative Example 4: On the basis of Example 6, the mass ratio of biochar to micron zero-valent iron ball milling was changed to 5:1, and the other conditions remained unchanged.
[0029] Comparative Example 5: On the basis of Example 6, the mass ratio of biochar to micron zero-valent iron ball milling was changed to 10:1, and the other conditions remained unchanged.
[0030] The structural characterization of the composite material prepared in the above embodiment is described below with reference to the accompanying drawings: (1) SEM images of the soybean dregs biochar and composite materials synthesized in Example 6 are shown in Figure 1 As shown in Figure 2, the surfaces of biochar and composite materials have abundant pore structures.
[0031] (2) The nitrogen adsorption-desorption curves of the soybean dregs biochar and composite material synthesized in Example 6 are shown in FIG. Figure 2 As shown in Figure 2, under 900℃ pyrolysis conditions, the specific surface area of potassium carbonate modified biochar reached 1363.1656 m 2 / g, the specific surface area of the composite material is 364.5442m 2 / g, which is beneficial to the adsorption of Cr (VI).
[0032] (3) Raman spectra of the composite materials synthesized in Examples 1 to 6 are shown in Figure 3 The composite material synthesized by pyrolysis of biochar at 800-900℃ has the highest ID / IG value, indicating that the material has a high degree of defect and electron transfer ability, which is conducive to the reduction of Cr (VI).
[0033] (4) The Fourier transform infrared spectra of the composite materials synthesized in Examples 1 to 6 are shown in Figure 4 As shown. 1245cm -1 The characteristic peak at is attributed to the stretching vibration of the CN bond, indicating that N atoms are successfully doped into the carbon network.
[0034] (5) The electrochemical impedance spectroscopy of the composite materials synthesized in Examples 1 to 6 is as follows: Figure 5 The composite material synthesized by pyrolysis of biochar at 900℃ has the smallest resistance and the best conductivity, which is beneficial to the transfer of electrons in the reaction system and the reduction of Cr (VI).
[0035] (6) The valence state of the Cr species on the surface of the composite material synthesized in Example 6 after reaction is as follows: Figure 6 After the reaction, Cr (III) is generated on the surface of the material, and the peak area of Cr (III) is greater than that of Cr (VI), indicating that the composite material can effectively reduce the Cr (VI) adsorbed on the surface.
[0036] (7) The changes of surface N species before and after the reaction of the composite material synthesized in Example 6 are as follows: Figure 7 After the reaction, the contents of pyridinic N and pyrrolic N on the surface of the composite material decreased significantly, indicating that they may be the main active sites for the adsorption and reduction of Cr (VI) by the composite material.
[0037] The following tests are conducted on the properties of the composite material prepared in the above embodiment in conjunction with the accompanying drawings: (1) The removal effect of composite materials prepared by biochar at different pyrolysis temperatures in Examples 1 to 6 on Cr (VI) in water: This experiment was conducted at room temperature. 40 ml of 40 mg / L Cr (VI) solution was added to a 50 ml centrifuge tube. The pH of the solution was adjusted to 5.6. 20 mg of composite materials prepared by biochar at different pyrolysis temperatures in Examples 1 to 6 were added and shaken on a shaker at 150 rpm. Samples were taken at certain time intervals and filtered through a 0.22 μm filter membrane to remove particulate matter. The Cr (VI) concentration was detected by diphenylcarbazide spectrophotometry (540 nm). The results are as follows: Figure 8 shown.
[0038] Depend on Figure 8 It can be seen that the composite material synthesized from the biochar prepared by pyrolysis at 900°C in Examples 1 to 6 has the best removal effect on Cr(VI), and its removal capacity for Cr(VI) can reach 77.96 mg / g.
[0039] (2) Effect of different iron-carbon ratio composite materials synthesized in Example 6 and Comparative Examples 1 to 5 on the removal of Cr (VI) in water: This experiment was conducted at room temperature. 40 ml of 40 mg / L Cr (VI) solution was added to a 50 ml centrifuge tube. The pH of the solution was adjusted to 5.6. 20 mg of different iron-carbon ratio composite materials synthesized in Example 6 and Comparative Examples 1 to 5 were added and shaken on a shaker at 150 rpm. Samples were taken at certain time intervals and filtered through a 0.22 μm filter membrane to remove particulate matter. The Cr (VI) concentration was detected by diphenylcarbazide spectrophotometry (540 nm). The results are as follows: Fig. 9 shown.
[0040] Depend on Fig. 9 It can be seen that the composite material (BC900) prepared with an iron-carbon ratio of 7:1 has the best removal effect on Cr (VI), and the removal capacity can reach 77.96 mg / g.
[0041] (3) Fig.10 This is a graph showing the effect of common cations in natural water on the removal of Cr (VI) by composite materials. + Outside, Ca 2+ 、Na + Mg 2+ (10 mg / L) had a certain inhibitory effect on the removal of Cr(VI) by the composite material. 2+ 、Na + Mg 2+The curve of the composite material (shown by the purple line in the figure) is higher than that of the control curve, which may be caused by the competitive adsorption of coexisting cations and Cr (VI). Nevertheless, the composite material (shown by the purple line in the figure) can still effectively remove Cr (VI) (88% to 98%).
[0042] (4) Fig.11 This is a graph showing the effects of common anions and organic matter in natural water on the removal of Cr (VI) by composite materials. - and SO4 2- The removal of Cr(VI) is inhibited, which may be attributed to the competitive adsorption between anions and hexavalent chromium. Anions will form coordination complexes with Fe(Ⅱ) on the surface of the material, thereby affecting the adsorption of Cr(VI). The addition of humic acid initially promoted the removal of Cr(VI), which may be due to the fact that the addition of humic acid lowered the pH value of the reaction system, which was beneficial to the adsorption of Cr(VI) by the material. On the other hand, as the reaction time increased, the removal of Cr(VI) was inhibited. This may be due to the fact that as the reaction proceeded, humic acid was enriched on the surface of the composite material and occupied the adsorption or reduction sites of Cr(VI).
[0043] (5) Fig.12 The effect of pH value on the removal of Cr (VI) by the composite material is shown in the figure. As shown in the figure, as the pH value increases from 3.2 to 10.2, the removal efficiency of Cr (VI) decreases from 100% to 44.8%. On the one hand, this is due to the fact that under acidic pH conditions, H + Increase, resulting in an increase in the positive charge on the surface of the material, while Cr(VI) is in the form of HCrO4 in the pH range of 2 to 6. - Exists, CrO4 above pH 6 2- Mainly. Therefore, acidic conditions enhance the electrostatic adsorption capacity between the composite material and Cr (VI). On the other hand, low pH accelerates the corrosion of Fe (0) in the composite material, effectively increasing the reaction rate of Cr (VI) adsorbed on the surface of the composite material with Fe (0) / Fe (II). On the contrary, under alkaline conditions, Cr (VI) and iron species can form a Fe (III) -Cr (III) hydroxide layer on the surface of the material, inhibiting the electron transfer process in the system.
[0044] (6) Fig.13 The effect of temperature on the removal of Cr (VI) from composite materials is shown in the figure. As shown in the figure, high temperature is conducive to the removal of Cr (VI). First, high temperature improves the mass transfer efficiency of the entire reaction and accelerates the collision and reaction between the material and the pollutant. In addition, the reaction between zero-valent iron and Cr (VI) is an endothermic process, and higher temperatures are conducive to the occurrence of the reaction.
[0045] (7) Table 1 is a comparison of the reduction effects of Cr (VI) by the composite material prepared in Example 6 and the reported materials. As shown in the table, compared with the similar materials reported, the material prepared in this patent has significant advantages in terms of removal efficiency and material dosage in removing Cr (VI).
[0046]
[0047]
[0048] In summary, the present invention aims to provide a method for preparing an endogenous nitrogen-doped biochar-zero-valent iron composite material with a high specific surface area. The method uses nitrogen-rich agricultural residue bean dregs as raw materials and potassium carbonate as a pore-forming agent to prepare endogenous nitrogen-doped biochar with a high specific surface area. Using micron zero-valent iron powder as the iron source, the biochar-zero-valent iron composite material was synthesized by ball milling technology, achieving rapid removal of Cr(VI) in water bodies. It has the characteristics of simple operation, low cost, high safety, and is suitable for large-scale production applications.
[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0050] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a highly active endogenous nitrogen-doped biochar-zero-valent iron composite material, characterized in that: The following steps are involved: (1) Taking agricultural residue bean curd residue as a precursor, washing it with deionized water for several times and then drying it, and grinding the dried bean curd residue into fine powder; (2) Weighing a certain amount of potassium carbonate and mixing it with the okara powder prepared in step (1) to form a solution, vigorously mixing the prepared potassium carbonate solution and the okara powder at room temperature for a certain period of time and then drying; (3) grinding the obtained dried product, placing the sample in a covered crucible and pyrolyzing it in an oxygen-limited environment of a muffle furnace to produce biochar; (4) The obtained biochar material is mixed with hydrochloric acid and stirred for a certain period of time to remove residual potassium carbonate, and the sample is repeatedly washed with deionized water until it is neutral; (5) Add micron zero-valent iron powder and biochar in a certain proportion into a planetary ball mill and grind them to obtain a composite material.
2. The method for preparing the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material according to claim 1, characterized in that: In steps (1) and (3), the ground products are sieved through a 100-mesh sieve.
3. The method for preparing the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material according to claim 1, characterized in that: In step (2), the mass ratio of potassium carbonate to okara powder is 2:
1.
4. The method for preparing the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material according to claim 1, characterized in that: In step (3), the calcination heating rate in the muffle furnace is 5-10°C / min, the calcination temperature is 400-900°C, and the calcination pyrolysis time is 2-4 hours.
5. The method for preparing the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material according to claim 1, characterized in that: In step (5), the mass ratio of the biochar to the micron zero-valent iron powder is 1:7, the ball milling time is 6 hours, the ball-to-material ratio is 20:1, the ball milling beads are made of zirconium oxide, and the ball milling beads have a diameter of 1-15 mm.
6. A high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material prepared by the method for preparing a high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material as described in any one of claims 1 to 5.
7. The high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material according to claim 6, characterized in that: The particle size of the composite material is 30-200 microns, and the specific surface area can reach 84.3792-364.5442m 2 / g.
8. An application of the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material as described in claim 7 in the environmental treatment of water pollution.
9. The use according to claim 8, characterized in that: The pollutant in the water body is Cr (VI).
10. The use according to claim 9, characterized in that: The concentration of Cr (VI) in the water body is 40 mg / L, and the degradation rate of Cr (VI) by the high-activity endogenous nitrogen-doped biochar-zero-valent iron composite material is as high as 100%, and the adsorption amount is 77.96 mg / g.
Citation Information
Patent Citations
Ball-milled zero-valent iron biochar composite material and preparation method and application thereof
CN112007608A
Micron zero-valent iron-loaded biochar for removing hexavalent chromium, and preparation method and application thereof
CN113173608A
Ball-milling modified charcoal loaded zero-valent iron composite material as well as preparation method and application thereof
CN114797746A
Preparation method and application of submicron carbon-iron composite material with high metal loading capacity
CN114870877A
Iron-copper bimetal modified biochar material as well as preparation method and application thereof
CN115518614A
